2004
DOI: 10.1002/cncr.20049
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of renal medullary carcinoma

Abstract: BACKGROUNDRenal medullary carcinoma is a rare kidney tumor with highly aggressive behavior. This tumor occurs exclusively in young patients with sickle cell trait or disease. To the authors' knowledge, very little is known to date regarding the underlying molecular genetics of this tumor, and no effective therapy has been established.METHODSThe authors analyzed the gene expression profiles of 2 renal medullary carcinomas from patients with sickle cell trait using microarrays containing 21,632 cyclic DNA (cDNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 88 publications
3
61
0
2
Order By: Relevance
“…10 Renal medullary carcinoma shares similarities with high-grade urothelial carcinoma with regard to its location, infiltrating pattern and tumor cell morphology. 15 Of interest is the case reported by Figenshau 16 that showed an association of renal medullary carcinoma and urothelial carcinoma. The authors speculated whether the finding represents a collision tumor or dedifferentiation of the pelvic urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…10 Renal medullary carcinoma shares similarities with high-grade urothelial carcinoma with regard to its location, infiltrating pattern and tumor cell morphology. 15 Of interest is the case reported by Figenshau 16 that showed an association of renal medullary carcinoma and urothelial carcinoma. The authors speculated whether the finding represents a collision tumor or dedifferentiation of the pelvic urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression profiling showed 487 genes to be expressed differently from that of other types of renal tumor, with an expression most closely resembling urothelial carcinoma. 25 In three cases FISH analysis showed amplification of the ABL gene, with increased expression of ABL protein in two cases. In this series no evidence of BCR-ABD translocation was detected, in contradiction to the report of Stahlschmidt et al 34 based on a single case.…”
Section: Renal Medullary Carcinomamentioning
confidence: 95%
“…33 The immunohistochemical expression of medullary carcinoma has been reported from several studies. 24,25,31 All tumors show positive and diffuse expression for cytokeratin AE1/AE3, low molecular weight cytokeratin, EMA, vimentin, HIF and VEGF. Cytokeratin 7 and carcinoembryonic antigen was focally expressed in all cases, whereas there was a variable expression of high molecular weight cytokeratin, Ulex europeaus agglutinin-1 and TP53.…”
Section: Renal Medullary Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate report, Yang et al suggested presence of hypoxia related and unrelated genetic abnormalities in significant number of cases, and hinted their role in the pathogenesis of RMC. 20 Recent studies looking into the cytogenetic abnormalities of RMC have failed to identify any consistent abnormalities across cases, and have also brought into question the aforementioned theory by Swartz on the grounds of cases in caucasian patients without hemoglobinopathies. 21,22 Gao et al, had recently shown involvement of genes in signaling pathways such as phosphatidylinositol 3-kinasePIK3C2G), cell cycle control (CDC25D and CDC73), and histone synthesis (HIST2H3D) based on molecular analysis of 11 patient specimens in a retrospective fashion.…”
Section: 10-17mentioning
confidence: 99%